Extension of Almost Contact Structure ( ϕ_4,ξ_4,η_4) on (Ν^(4n+3)⨂R^d)≅ M^(5n+4) - Kumar, Nand Kishor (Ganeshman Darpan, 2024)
A prior research of almost contacts on 1, 2, and 3-manifolds has been partially investigated. On the other hand, the existence and geometry of a virtually contact 4-structure are poorly understood. A class of almost contact structures, g c d (2, n) = 1, has been created in this article. It is related to an almost compact 3-structure carried on a smooth Riemannian metric manifold (M, ) of dimension (5n + 4). Using the almost contact metric manifold ( , ) as a starting point, we have demonstrated the existence of an almost contact structure on () from ( for i = 1,2,3 on , constructed as a linear combinations.